The family factor - Hartman, Henry; Brown, Lisa.; Starlink Project; Texas Higher Education Coordinating Board. Community and Technical Colleges Division; Dallas County Community College District (Dallas, Tex. : Starlink, 2009)
This program focuses on an instructional approach to student retention, success and persistence, particularly Latino students. The video explores the impact of engaging students' families in college coursework with the students, family, faculty and administrators whose experiences provide a unique insight into instruction that works.
Introduction by Dr. Gerardo E. de los Santos.
Recorded on February 23, 2009.
Keywords: Hispanic American college students; Education, Higher -- Parent participation -- United States; Academic achievement; Motivation in education; DVD-Video discs; Video recordings for the hearing impaired